2022
DOI: 10.3390/nu14132562
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Blueberry Consumption on Cardiovascular Health in Healthy Adults: A Cross-Over Randomised Controlled Trial

Abstract: Blueberries are rich in polyphenols, and their effect on cardiovascular health, including risk factors for endothelial dysfunction and hypertension, has been investigated in interventional studies. However, the difference between blueberry treatments in varied forms for their cardiovascular-protective effect remains poorly understood. The current study assessed the effects of whole blueberry and freeze-dried blueberry powder compared to a control on cardiovascular health in young adults. A cross-over randomise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 51 publications
2
16
1
Order By: Relevance
“…A venous blood samples were taken ∼3 h after ingestion of supplement and immediately centrifuged at 1160 g and 4°C for 10 min (ettich® 320 centrifuge, Canada). Plasma was then extracted and stored in labelled tubes at −80°C for later analysis of to assess plasma NO 3 ‐ and NO 2 ‐ concentrations using a modification of the chemiluminescence technique via chemiluminescence analyser (the Sievers NOA 280i, Analytix, UK) as described elsewhere (Shannon et al, 2016; Wang et al, 2022). Pre‐ and post‐BLa sample was taken from the pad of the index finger of the left hand and analysed using the Lactate Pro‐2 (Lactate Pro analyser, Arkay, Kyoto, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…A venous blood samples were taken ∼3 h after ingestion of supplement and immediately centrifuged at 1160 g and 4°C for 10 min (ettich® 320 centrifuge, Canada). Plasma was then extracted and stored in labelled tubes at −80°C for later analysis of to assess plasma NO 3 ‐ and NO 2 ‐ concentrations using a modification of the chemiluminescence technique via chemiluminescence analyser (the Sievers NOA 280i, Analytix, UK) as described elsewhere (Shannon et al, 2016; Wang et al, 2022). Pre‐ and post‐BLa sample was taken from the pad of the index finger of the left hand and analysed using the Lactate Pro‐2 (Lactate Pro analyser, Arkay, Kyoto, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…44 However, the body of literature on the antihypertensive effects of blueberries is mixed such that equal numbers of studies have demonstrated benefits and null effects. 44,45,73,74,76,77,[95][96][97] The reason(s) contributing to the discrepancies between our studies cannot be determined at this time. However, one possible contributing factor is the difference in the study population as the present study was performed in Colorado vs. Florida previously, 44 and there could be differences in the health status, physiology, and/or lifestyle factors.…”
Section: Food Function Papermentioning
confidence: 98%
“…This is mainly due to their rich polyphenol content; they have shown a high antioxidant capacity in vitro, characterised by various types of phytochemicals, including abundant anthocyanin pigments [ 12 ]. A number of epidemiological studies and RCTs have linked the regular consumption of blueberries and/or anthocyanins with a reduced risk of cardiovascular disease, obesity, type 2 diabetes, neuroprotection and cognitive maintenance [ 13 , 14 , 15 , 16 ]. Freeze drying is one of the most commonly used methods for their preservation and consumption [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Freeze drying is one of the most commonly used methods for their preservation and consumption [ 12 ]. The aim of the present study was to characterise the consistency of the variation in multiple endpoints in response to the blueberry interventions that we have recently published [ 13 ], and to use the urinary metabolomic differences between responders (RS) and non-responders (NRS) in the intervention to identify predictors of the response.…”
Section: Introductionmentioning
confidence: 99%